Status epilepticus induces chronic silencing of burster and dominance of regular firing neurons during sharp wave-ripples in the mouse subiculum - Lippmann, Kristina; Klaft, Zin-Juan; Salar, Seda; Hollnagel, Jan-Oliver; Valero, Manuel; Maslarova, Anna (Neurobiology of disease, 2022)
Sharp wave-ripples (SWRs) are hippocampal oscillations associated with memory consolidation. The subiculum, as the hippocampal output structure, ensures that hippocampal memory representations are transferred correctly to the consolidating neocortical regions. Because patients with temporal lobe epilepsy often develop memory deficits, we hypothesized that epileptic networks may disrupt subicular SWRs. We therefore investigated the impact of experimentally induced status epilepticus (SE) on subicular SWRs and contributing pyramidal neurons using electrophysiological recordings in mouse hippocampal slices. Subicular SWRs expressed hyperexcitable features post-SE, including increased ripple and unit activity. While regular firing neurons normally remain silent during SWRs, selective disinhibition recruited more regular firing neurons for action potential generation during SWRs post-SE. By contrast, burster neurons generated fewer action potential bursts during SWRs post-SE. Furthermore, altered timing of postsynaptic and action potentials suggested distorted neuronal recruitment during SWRs. Distorted subicular SWRs may therefore impair information processing and memory consolidation in epilepsy.
Online verfügbar 21 November 2022, Artikelversion 24 November 2022
Gesehen am 31.01.2023